Detection of Invertebrate Suppressive Soils, and Identification of a Possible Biological Control Agent for Meloidogyne Nematodes Using High Resolution Rhizosphere Microbial Community Analysis - Bell, Nigel L.; Adam, Katharine H.; Jones, Rhys J.; Johnson, Richard D.; Mtandavari, Yeukai F.; Burch, Gabriela; Cave, Vanessa; Cameron, Catherine; Maclean, Paul; Popay, Alison J.; Fleetwood, Damien (Frontiers in Plant Science, 2016)
White clover (Trifolium repens) is the key legume component of New Zealand pastoral agriculture due to the high quality feed and nitrogen inputs it provides. Invertebrate pests constrain white clover growth and this study investigated rhizosphere-associated fungal controls for two of these pests and attempts to disentangle the underpinning mechanisms. The degree of suppressiveness of ten soils, in a latitudinal gradient down New Zealand, to added Meloidogyne hapla and Costelytra zealandica scarab larvae was measured in untreated soil. Most of the soils showed no suppressive activity against these pests but two showed activity against M. hapla and two against C. zealandica. Rhizosphere fungi responsible for pest suppressive responses were elucidated via next-generation sequencing. In the M. hapla-suppressive soils nematode-trapping Orbiliomycetes fungi were present in significantly greater abundance than non-suppressive soils and their abundance increased further with addition of M. hapla. A comparison of plant growth and the rhizosphere fungal community between untreated and irradiated soil was carried out on five of the ten soils using Pyronota as the scarab larvae. Soil irradiation either: reduced (by 60–70%); increased (16×) or made no difference to white clover growth across the five soils tested, illustrating the range of microbial impacts on plant production. In one of the M. hapla suppressive soils irradiation resulted in a significant increase in nematode galling suggesting that Orbiliomycetes fungi were indeed responsible for the suppressive effect. Lack of consistent changes in soil macronutrients and pH post-irradiation suggest these were not responsible for plant or invertebrate responses. The use of next generation sequencing in controlled pot trials has allowed identification of a potential biological control organism and bioindicator for M. hapla suppression.